AFLP analysis of African cassava (Manihot esculenta Crantz) germplasm resistant to the cassava mosaic disease (CMD) - Fregene, Martin A.; Bernal, A.; Duque E., Myriam Cristina; Dixon, Alfred G.O.; Tohme, Joseph M. (Springer, 2000)
Amplified fragment length polymophism was assessed in 20 land races and nine elite lines of cassava from Africa, resistant and susceptible to the cassava mosaic disease (CMD). Eleven accessions from a representative core collection from Latin America, previously studied by AFLPs, were included as a reference. AFLP data from all accessions was analyzed by both the unweighted pair group mean average (UPGMA) and multiple cluster analysis (MCA) methods of analysis. Genetic differentiation between clusters and the coefficient of genetic differentiation was also calculated. Results reveal a genetic divergence between African and Latin American accessions, although some overlap was found between them. African land races resistant to CMD, were also found to be genetically differentiated from susceptible land races and from resistant elite lines. AFLP analysis identified a considerable number of duplicates in the African accessions, suggesting a sizeable percentage of redundancy. A unique AFLP fragment, found in a relatively high frequency in African accessions, but absent in the Latin American accessions, was found to be associated with branching pattern by QTL mapping in an F1 progeny derived from African and Latin American parents. The likely source and the utility of the unique AFLP fragment in understanding the processes of genetic divergence in Africa is discussed.